The self and the impossible pursuit of justice in J.M. Coetzee's "Waiting for the barbarians, disgrace and foe" - Swanepoel, Elbie (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics)
In its engagement with J.M. Coetzee's Waiting for the Barbarians, Disgrace and Foe, this thesis explores how the philosophies of Emmanuel Levinas and Jacques Derrida can be used as a framework for understanding the self's relationship with the other. In contrast to postcolonial readings of these texts, this thesis does not consider the separation between the self and the other in terms of social or cultural differences but rather the radical alterity of the other that is perceived in the face-to-face encounter. This study aims to illustrate how the engagement with alterity exposes the instability of the self's structures of knowledge that, in these instances, are grounded in the Western metaphysical tradition. The effects of the self's encounter with the other are seen in the personal transformation of Coetzee's protagonists whose initial flaws and problematic worldviews are revealed in the context of the injustices done to the other. Furthermore, the study examines the extent to which the self is complicit in the suffering of the other and how this ultimately complicates their pursuit of justice for them. While the focus of this thesis is primarily on the characters, it also shows how the writer's careful treatment of otherness functions to confront and engage the reader with the alterity of the other and the ethical dilemmas inherent in attempting to conceptualise it. The study concludes that the protagonists' engagement with others and their subsequent confrontation with themselves lead them to consider what an ethical response to the other might be. This ethical turn results in positive change, however ambiguously, in their thoughts about and behaviours toward other beings.
Keywords: Coetzee, J M, 1940- -- Criticism and interpretation; Coetzee, J M, 1940- -- Waiting for the barbarians; Coetzee, J M, 1940- -- Disgrace; Coetzee, J M, 1940- -- Foe; Ethics in literature; Deconstruction; Postmodernism (Literature); Justice in literature